Koncentrácia ortute vo vzorkách vciel a medu, pochádzajúcich z priemyselne exponovanej a neexponovanej oblasti - Toporcák, J; Legáth, J; Kul'ková, J (Veterinarni medicina, 1992)
Increasing numbers of specialists have been concerned with the problem of friendly environment in relation to man as well as to farm and wild animals. Greater interest in the biological monitoring of environment and ecosystem contamination can be observed. Determination of residues of organic and inorganic substances in bees (Apis mellifera) and in their products is one of effective possibilities of environmental pollution monitoring. Our work was aimed at the study of mercury levels in bees and their products. Mercury levels were determined in the head, abdomen and thorax of bees (Apis mellifera) from 20 bee populations coming from industrially contaminated areas with a dominant load of mercury (10 populations) and from uncontaminated areas. Mercury levels were determined simultaneously in honey coming from both contaminated and uncontaminated areas. The following mercury levels were found in bees from the contaminated area: heads 0.029-0.385 mg/kg, thorax 0.028-0.595 mg/kg and abdomen 0.083-2.255 mg/kg. Mercury levels in samples from uncontaminated areas ranged from 0.004 to 0.024 mg/kg in the heads, from 0.004 to 0.008 mg/kg in the thorax and from 0.008 to 0.020 mg/kg in the abdomen. In honey samples from the contaminated and uncontaminated areas mercury levels ranged from 0.050 to 0.212 mg/kg and from 0.001 to 0.003 mg/kg, respectively. The results of sample analyses for mercury loads in bees and honey from both contaminated and uncontaminated areas are given in Tab. I. Mean mercury levels in the single parts of the body in Apis mellifera and in honey from contaminated and uncontaminated areas are given in Figs. 1, 2, 3.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Animals; včely; rtuť; Mercury; znečištění životního prostředí; Environmental Pollution; zvířata; med; Czechoslovakia; Environmental Monitoring; Honey; Bees; monitorování životního prostředí; Československo